The behaviour and charging dynamics of concentrated electrolytes in confinement under potential control - Southam, A (2022)
The current understanding of intermolecular and interfacial forces in concentrated electrolytes is limited. Their importance to fields such as medicine, biology, ecology and the energy industry means that the pursuit of better knowledge has a wide-ranging impact on other areas of science and technology. In particular, the ubiquitous nature of batteries and energy-storing devices makes the behaviour of concentrated electrolytes near charged surfaces of special interest. This thesis presents two novel surface force balance (SFB) methods to measure surface forces across electrolytes confined between charged surfaces, where one or both of the surfaces are under electrochemical control. The first method combines a muscovite mica surface and an ultra-smooth gold surface (gold/mica SFB), and the second uses two ultra-smooth gold surfaces. A large part of this work is concerned with the use of gold to fulfil the triple role of confining surface, working electrode and interferometric mirror. Improvements to surface fabrication methods yielded unique high-resolution (∼ 0.1 nm) force measurements in the gold/mica setups and electrochemical measurements where the gold surfaces were under potential control. These setups were used to measure force profiles in an ionic liquid (IL), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (C4C1pyrr TFSI), and in a dilute electrolyte, potassium chloride in water (KCl (aq)) at 1.5 mM and 0.6 mM concentrations. In the gold/mica setup, unprecedented resolution was achieved, as evidenced by the presence of molecular layering in the force profiles.